Do applicants' prior experiences influence organizational attractiveness prediction? - Gomes, D. R.; Neves, J. (Management Research: The Journal of the Iberoamerican Academy of Management, 2010)
Purpose – The paper aims to clarify some incongruence between theoretical established grounds, that assume that an applicants' assessment of organizations is constrained by individual contextual factors, and dubious empirical findings. It seeks to propose that previous work experience (PWE) and previous response to job advertisements experience (PRA) interact with the vacancy elements of job and organizational attributes (OA) for the prediction of organizational attractiveness. Design/methodology/approach – An adapted employment advertisement describing a job and an organization was presented to 227 participants from the marketing area (72 professionals and 155 marketing undergraduates), who were asked to respond to a questionnaire containing the measures of the study variables. The hypotheses were tested using linear regression methodology. Findings – Empirical evidence showed that the assessment of the vacancy is constrained by individual contextual factors. PWE and PRA moderated the relation between the OA and attractiveness. PRA moderated the relation between perceived knowledge of results (KR) of the job and attractiveness. Practical implications – The results imply different job searching profiles according to the type of applicants' prior experiences. A more experienced profile of applicants appears to have a job?searching strategy based on the KR of the job itself and on the type of OA. A more junior profile appears to have a job?searching strategy focused on the organization, and less related with the job itself. Originality/value – Theoretically, the paper discusses the influences of individual context factors in organizational attraction. Empirically, it provides evidence of the role of applicants' previous experiences when assessing organizations. In practical terms, it discusses directions towards employee attraction activities.?